Reframing Digital Competencies for Hospitality Educators in the Era of Society 5.0: A Pedagogical Integration Framework - Nor Roselidyawaty Rokeman,; Che Ghani Che Kob,; Mohd Nasir Mohd Yaacob, (Journal of TVET and Technology Review, 2026)
The rapid evolution of digital technologies and the emergence of Society 5.0 have significantly transformed the landscape of higher education, particularly in practice-oriented disciplines such as hospitality education. As human-centred, technology-integrated ecosystems redefine industry operations, hospitality educators are required to possess advanced digital competencies that extend beyond basic technological literacy. However, existing digital competency models remain largely generic and inadequately contextualized for hospitality pedagogy, resulting in a gap between technological advancement and instructional practice. This study aims to reframe digital competencies for hospitality educators by developing a pedagogical integration framework aligned with the principles of Society 5.0. The research adopts a mixed-method design comprising a systematic literature review and expert consensus through a Modified Delphi technique involving specialists in hospitality education, educational technology, and curriculum development. The findings identify key competency domains, including AI literacy, digital pedagogical design, immersive technology integration, data-informed instructional decision-making, and ethical-technological governance. The proposed framework demonstrates conceptual coherence and expert validity, offering a structured model to guide curriculum enhancement, professional development, and institutional policy planning. In conclusion, the study contributes a context-specific, future-oriented digital competency framework that supports the transformation of hospitality education towards a Society 5.0-ready pedagogical ecosystem.